The Waqf As Solution to Achieving SDGs 3 - Syamsuri, Syamsuri; Novandi Nurtajuddin, Akhmad; Nurfattah, Arizqiya (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
The SDGs, as an effort to save the earth and improve human welfare, is the responsibility of all levels of society. The purpose of this study is to examine the concept of using waqf to solve health problems by establishing waqf-based health facilities and health services, and to examine the concept of its application in Indonesia. And the research method used is qualitative with literature study, in this study examined various secondary data sources in the form of documents, journals and articles related to the topic under study. The conclusion of this study shows that how to use waqf as a solution to the problem of poverty, which was launched in the 3rd SDG as a health solution for the poor. The concept of using waqf in the construction and operational support of health facilities does not violate the applicable PERPU. Therefore, the idea is in line with Article 170 of Law No. 36/2009 on health and Presidential Regulation No. 59/2017 on SDGs or sustainable development. If the concept of waqf and the applicable regulations are harmonised, the government can build sustainable and inclusive waqf-based health facilities.